PENGARUH PELATIHAN KERJA TERHADAP KINERJA KARYAWAN - Ghina Ulayya Hidayat; Deslita Kayla Nasywa, Sandi Dian Saputra, Sulistiasih (CV. Adiba Aisha Amira, 2024)
Companies need to continuously improve employee performance in this fast-paced and cutthroat business environment to remain relevant and face new challenges. Training is one method that has been successful in improving employee performance. Employee performance can be improved and their effectiveness in carrying out their work can be increased through training that increases their knowledge, skills and competencies. The purpose of this research is to find out how job training can influence employee performance in a company. This research uses the literature review method to collect, analyze and obtain a general view regarding the effect of job training on employee performance. Through this research, it can be seen that there is a significant influence of job training on employee performance, namely that employees can work professionally in their field, improve employee skills and abilities, increase work motivation, and improve work discipline.